Structure-based design of an antibacterial peptide from the Myotoxin II sequence, evaluating its effectiveness against Gram-negative bacteria and its safety - Tatiana Huertas; Diana Millán; Angela V. Fonseca-Benítez; James Guevara-Pulido (Scientific Reports)
Abstract Bacterial resistance poses a significant public health challenge, particularly for pathogens prioritized by the World Health Organization, such as carbapenem-resistant Escherichia coli. There has been growing interest in exploring animal toxins as potential alternatives to antibiotics. This study centers on the rational design of an antibiotic peptide based on the sequence 115–129 from Myotoxin II, sourced from the venom of the snake Bothrops asper. We modified the original sequence 20 times using molecular docking and found that peptide sequence 20 (KHWYKHYRH) exhibited the highest affinity energy of − 7.6 kcal/mol for lipopolysaccharide (LPS). The in vitro potency was assessed against E. coli, with an IC50 of 0.27 mg/mL, while P. aeruginosa (ATCC 27853) showed an IC50 of 2.93 mg/mL. Conversely, the peptide was ineffective against resistant strains, such as the NDM-1-positive Klebsiella pneumoniae (ATCC BAA-2146) and the ESBL clinical isolate E. coli (CTX-M). Additionally, the safety of peptide 20 was evaluated, revealing that none of the tested concentrations caused hemolytic activity or loss of cellular viability in L929 and Caco-2 cells. This indicates that rational, structure-based design is an effective strategy for developing safe peptides.